2021
DOI: 10.1037/com0000286
|View full text |Cite
|
Sign up to set email alerts
|

Food calls enhance visual discrimination learning in chimpanzees (Pan troglodytes verus).

Abstract: Social learning is of universal importance to animal life and communication is likely to foster it. How do animals recognise when others produce actions that lead to relevant new information? To address this, we exposed four chimpanzees to an arbitrary learning task, a two-choice visual discrimination paradigm presented on a touch screen that led to food rewards. In each trial, images were paired with one of four acoustic treatments: 1) relevant or 2) irrelevant chimpanzee calls ('rough grunts' to food; 'pant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Clearly, conspecific cues, such as food consumption, allow them to gather information as to the potential palatability of novel items. However, chimpanzees also produce acoustic signals, that is, FC, which are known to recruit group members to food patches (Kalan & Boesch, 2015), guide foraging efforts (Slocombe & Zuberbühler, 2005), and according to the results of our recent companion study, improve visual discrimination in food‐related tasks (Déaux et al, 2021). Thus, chimpanzee FC could either serve as gating cues that prepare for a learning opportunity (the social facilitation hypothesis) or as direct cues that trigger social‐learned food preferences, similar to how alarm calls have been shown to trigger learning (Griffin, 2004).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Clearly, conspecific cues, such as food consumption, allow them to gather information as to the potential palatability of novel items. However, chimpanzees also produce acoustic signals, that is, FC, which are known to recruit group members to food patches (Kalan & Boesch, 2015), guide foraging efforts (Slocombe & Zuberbühler, 2005), and according to the results of our recent companion study, improve visual discrimination in food‐related tasks (Déaux et al, 2021). Thus, chimpanzee FC could either serve as gating cues that prepare for a learning opportunity (the social facilitation hypothesis) or as direct cues that trigger social‐learned food preferences, similar to how alarm calls have been shown to trigger learning (Griffin, 2004).…”
Section: Discussionmentioning
confidence: 96%
“…Facilitating, or gating, social learning of foraging behaviors. In a recent study with chimpanzees, we partially addressed the social facilitation learning hypothesis by showing that naïve animals were faster at learning a visual discrimination task (leading to food rewards) if they were primed with FC compared with other calls (Déaux et al, 2021). We concluded that FC may enhance the attention of listeners and thus enhance their ability and readiness to learn novel visual information.…”
Section: Introductionmentioning
confidence: 99%
“…Frequent and even daily usage of computer touchscreens by great apes, often in front of zoo guests, began at the Smithsonian National Zoo Orangutan ThinkTank [8] and has since become a routine activity for great apes at Lincoln Park Zoo [9], Kyoto City Zoo [10], Zoo Atlanta [11], and Indianapolis Zoo [12]. Touchscreen tasks have also been used consistently, but less frequently, with great apes at Leipzig Zoo [13], Edinburgh Zoo [14], Basel Zoo [15], and Detroit Zoo [16]. These cases often involve zoo-academia collaborations [17]; the methods typically include tasks and equipment formerly developed and refined in university laboratory settings to produce publishable findings on primate cognition.…”
Section: Introductionmentioning
confidence: 99%